2014
DOI: 10.1002/ar.22998
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin‐A3 and Ephrin‐A4 Contribute to Microglia‐Induced Angiogenesis in Brain Endothelial Cells

Abstract: The association of microglia with brain vasculature during development and the reduced brain vascular complexity in microglia-deficient mice suggest the role of microglia in cerebrovascular angiogenesis. However, the underlying molecular mechanism remains unclear. Here, using an in vitro angiogenesis model, we found the culture supernatant of BV2 microglial cells significantly enhanced capillary-like tube formation and migration of brain microvascular endothelial cells (BMECs). The expression of angiogenic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Some other factors secreted by microglia, such as protease serine 2, brain-derived neurotrophic factor, and glial cell line-derived neurotrophic factor, can also promote neurogenesis [98]. Furthermore, microglia upregulate endothelial ephrin-A3 and ephrin-A4 expression to facilitate in vitro angiogenesis of brain endothelial cells [99]. These studies provide evidence that microglia may promote neurogenesis and angiogenesis, which are beneficial for brain function recovery.…”
Section: Microgliamentioning
confidence: 99%
“…Some other factors secreted by microglia, such as protease serine 2, brain-derived neurotrophic factor, and glial cell line-derived neurotrophic factor, can also promote neurogenesis [98]. Furthermore, microglia upregulate endothelial ephrin-A3 and ephrin-A4 expression to facilitate in vitro angiogenesis of brain endothelial cells [99]. These studies provide evidence that microglia may promote neurogenesis and angiogenesis, which are beneficial for brain function recovery.…”
Section: Microgliamentioning
confidence: 99%
“…In primary rat cerebral endothelial cultures, TNFα potently increased EPO receptor expression; further exposure to EPO in TNFα-treated cells significantly promoted matrigel tube formation, whereas blocking TNFR1 dampened TNFα-induced EPO receptor levels and prevented EPO-induced tube formation (Wang et al 2011b). Recently, it has been proposed that microglia enhanced in vitro angiogenesis of brain microvascular endothelial cells by releasing TNFα and upregulating the expression of angiogenic factors ephrin-A3 and ephrin-A4 (Li et al 2014). Altogether, these data are consistent with the idea that TNFα may act as a remodeling signal within the recovering neurovascular unit.…”
Section: Extracellular Signals Within the Neurovascular Unit For Nmentioning
confidence: 99%
“…Recent studies suggested that microglia regulate vascular branching and proliferation via release of soluble mediators which either promote or inhibit vascular network formation (Arnold and Betsholtz, 2013; Stefater et al, 2011). More recently, microglia have been shown to facilitate angiogenesis in vitro via release of tumor necrosis factor-α (TNF-α), which upregulates endothelial ephrin-A3 and ephrin-A4 (Li et al, 2014). Moreover, microglia are endowed with neurotransmitter receptors including iono-and metabo-tropic Glu receptors (Pocock and Kettenmann, 2007) and are reactive to neural activity (Hung et al, 2010; Wake et al, 2009).…”
Section: Possible Mechanisms Underlying Activity-induced Cerebrovmentioning
confidence: 99%